Brief communication: Effects of conditioned media from human platelet lysate cultured MSC on osteogenic cell differentiation in vitro - Shanbhag, Siddharth; Al-Sharabi, Niyaz; Mohamed-Ahmed, Samih; Gruber, Reinhard; Kristoffersen, Einar K.; Mustafa, Kamal (Frontiers in Bioengineering and Biotechnology, 2022)
Culturing mesenchymal stromal cells (MSC) in human platelet lysate (HPL) supplemented media can enhance their osteogenic differentiation potential. The objective of this study was to test the hypothesis that conditioned media (CM) derived from HPL-cultured MSC also have pro-osteogenic effects. Pooled CM was prepared from HPL-cultured human bone marrow MSC (BMSC) of multiple donors and applied on BMSC of different donors (than those used for CM preparation), with or without additional supplementation (HPL, fetal bovine serum (FBS)) and osteogenic stimulation. At various time-points, cell proliferation, alkaline phosphatase (ALP) activity, osteogenic gene expression and in vitro mineralization were assessed. BMSC in standard unstimulated growth media served as controls. After 3-7 days, CM alone did not promote BMSC proliferation or ALP activity; supplementation of CM with HPL slightly improved these effects. After 2 and 7 days, CM alone, but not CM supplemented with HPL, promoted osteogenic gene expression. After 14 days, only CM supplemented with FBS and osteogenic stimulants supported in vitro BMSC mineralization; CM alone and CM supplemented with HPL did not support mineralization, regardless of osteogenic stimulation. In summary, CM from HPL-cultured BMSC promoted osteogenic gene expression but not in vitro mineralization in allogeneic BMSC even when supplemented with HPL and/or osteogenic stimulants. Future studies should investigate the role and relevance of supplementation and osteogenic induction in in vitro assays using CM from MSC.